Odpowiedź:
1.
a) (2a−4b)² = 4a² -16ab + 16b²
b) (3a+32b)² = 9a² + 192ab + 1024b²
c) (−2x−3b)² = 4x² + 12xb + 9b²
d) (−3b+34a)² = 9b² - 204ba + 1156a²
2.
a) 4x²+8x+4 = (2x + 2)²
b) 49x²−70xz+25z² = (7x-5z)²
3.
a) 4x²−81y² = (2x - 9y) * (2x + 9y)
b) 5x²−179y² = ([tex]\sqrt{5}[/tex]x - [tex]\sqrt{179}[/tex]y) * ([tex]\sqrt{5}[/tex]x + [tex]\sqrt{179}[/tex]y)
4.
(x+3y)(x−3y)+(x+2y)²−(2x²−5y²) = x² - 9y² + x² + 4xy + 4y² -2x² + 5y² = 4xy
x = [tex]\sqrt{8}[/tex]
y = [tex]\sqrt{2}[/tex]
4 * [tex]\sqrt{8}[/tex] * [tex]\sqrt{2}[/tex] = 4[tex]\sqrt{16}[/tex]
Szczegółowe wyjaśnienie: